PERLINDUNGAN HUKUM TERHADAP PEMILIK MEREK TIDAK TERDAFTAR DITINJAU DARI PRINSIP “USE IN COMMERCE” - Yohan Prawira Pakpahan; Imam Haryanto (Faculty of Law, Maranatha Christian University, 2021)
“A trademark may be a sign that features a distinguishing power and is employed within the context of trading goods or services. In Indonesia, trademarks are protected supported the primary registrant protection system or constitutive principle. The protection system states that a protected brand may be a trademark that has been registered with the Directorate General of belongings or trademarks declared as well-known trademark. the matter that happens is said as to whether there's protection for ordinary trademark that don't seem to be registered when there are parties who aren't accountable for registering the trademark, in order that the rights to the trademark are given to parties who aren't the particular owners of the trademark. this suggests that the law only provides protection to the primary person to register. supported that, they get the exclusive rights and show that they're truth owner. Situation like this protects false registration and provides false protection. The trademark protection mechanism in America doesn't implement this type of protection. America uses the protection supported the utilization as a practical, which is should fulfill the necessities, prefer it should be employed in commerce or will be utilized in commerce. For trademarks that haven't yet been registered, Indonesia should implement a protection system implemented by the United States. that helps protect unregistered trademarks if they need been utilized in trade”.Keywords: Constitutive Principle, Trademarks, Use In Commerce